Dietary fiber intervention on gut microbiota composition in healthy adults: a systematic review and meta-analysis. Issue 6 (11th May 2018) - So, Daniel; Whelan, Kevin; Rossi, Megan; Morrison, Mark; Holtmann, Gerald; Kelly, Jaimon T; Shanahan, Erin R; Staudacher, Heidi M; Campbell, Katrina L
ABSTRACT: Background: Dysfunction of the gut microbiota is frequently reported as a manifestation of chronic diseases, and therefore presents as a modifiable risk factor in their development. Diet is a major regulator of the gut microbiota, and certain types of dietary fiber may modify bacterial numbers and metabolism, including short-chain fatty acid (SCFA) generation. Objective: A systematic review and meta-analysis were undertaken to assess the effect of dietary fiber interventions on gut microbiota composition in healthy adults. Design: A systematic search was conducted across MEDLINE, EMBASE, CENTRAL, and CINAHL for randomized controlled trials using culture and/or molecular microbiological techniques evaluating the effect of fiber intervention on gut microbiota composition in healthy adults. Meta-analyses via a random-effects model were performed on alpha diversity, prespecified bacterial abundances including Bifidobacterium and Lactobacillus spp., and fecal SCFA concentrations comparing dietary fiber interventions with placebo/low-fiber comparators. Results: A total of 64 studies involving 2099 participants were included. Dietary fiber intervention resulted in higher abundance of Bifidobacterium spp. (standardized mean difference (SMD): 0.64; 95% CI: 0.42, 0.86; P < 0.00001) and Lactobacillus spp. (SMD: 0.22; 0.03, 0.41; P = 0.02) as well as fecal butyrate concentration (SMD: 0.24; 0.00, 0.47; P = 0.05) compared with placebo/low-fiber comparators. Subgroup analysis revealed that fructans and galacto-oligosaccharides led to significantly greater abundance of both Bifidobacterium spp. and Lactobacillus spp. compared with comparators ( P < 0.00001 and P = 0.002, respectively). No differences in effect were found between fiber intervention and comparators for α-diversity, abundances of other prespecified bacteria, or other SCFA concentrations. Conclusions: Dietary fiber intervention, particularly involving fructans and galacto-oligosaccharides, leads to higher fecal abundance of Bifidobacterium and Lactobacillus spp. but does not affect α-diversity. Further research is required to better understand the role of individual fiber types on the growth of microbes and the overall gut microbial community. This review was registered at PROSPERO as CRD42016053101.